Topic modeling three decades of climate change news in Denmark - Meier, Florian; Eskjær, Mikkel Fugl (Frontiers in Communication, 2024)
Climate change is a dynamic and rapidly evolving media agenda. First associated with scientific notions of the greenhouse effect, it was later presented as global warming before reaching the current and broader picture of climate change. Over its development, climate change reporting has touched on a broad range of topics reflecting shifting scientific understandings, political interventions, and public anxieties, all of which condition the public's view and actions on climate change. To better understand which issues the Danish public has been exposed to, this study uses topic modelling to analyse 32 years of climate change communication in Denmark (1990Denmark ( -2021, n=63,743), n=63,743). It identifies 85 topics grouped into 14 themes dealing with climate change in Danish national media outlets. Topics differ in prevalence and longitudinal stability while reflecting outlet bias in political leaning and communicative modalities. The most pronounced differences in climate change reporting are between public service media and traditional newspapers. This indicates that media users relying mainly on online news from public service providers, without additional access to print media, will receive information on climate change that is more topical and less politicised, more thematic and less structural, more about high-level politics than everyday interventions and more concerned with consequences than solutions.